Pengaruh Profesionalisme, Independensi Auditor dan Etika Profesi Terhadap Kinerja Auditor - Yusuf, Fadel; Surianti, Meily; Deliana, Deliana; Sembiring, Rahmat Widia (Jurnal Akuntansi dan Keuangan, 2025)
This research aims to determine whether Professionalism, Auditor Independence, and Professional Ethics affect Auditor Performance. The research method employed is quantitative research. The population in this study consists of 138 auditors working at Public Accounting Firms in Medan City. The sample in this study uses a purposive sampling technique with criteria for auditors working at Public Accounting Firms in Medan, auditors with a minimum position as senior auditors, and auditors who have worked for at least one year. This research uses a survey method with primary data obtained from questionnaires. The data analysis technique used in this study is a quantitative analysis technique using the statistical software Smart PLS (Partial Least Square). The results of this study show that Professionalism has a positive effect on Auditor Performance. Auditor Independence has a positive effect on Auditor Performance. Professional Ethics has a positive effect on Auditor Performance.